2018
DOI: 10.1111/nph.15032
|View full text |Cite
|
Sign up to set email alerts
|

Water uptake can occur through woody portions of roots and facilitates localized embolism repair in grapevine

Abstract: Water acquisition is thought to be limited to the unsuberized surface located close to root tips. However, there are recurring periods when the unsuberized surfaces are limited in woody root systems, and radial water uptake across the bark of woody roots might play an important physiological role in hydraulic functioning. Using X-ray microcomputed tomography (microCT) and hydraulic conductivity measurements (Lp ), we examined water uptake capacity of suberized woody roots in vivo and in excised samples. Bark h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…At least two other phenomena may contribute to current release that is higher than expected. Firstly, Cuneo et al (2018) show that, although woody portions of roots act as an electrical barrier (also to microbial degradation), exchanges may occur during water uptake (in order to facilitate localized embolism repair in grapevines). Secondly, as discussed also in the introduction, some roots show anisotropic electrical conductivity, allowing current to flow radially more easily than longitudinally (Anderson and Higinbotham, 1976).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least two other phenomena may contribute to current release that is higher than expected. Firstly, Cuneo et al (2018) show that, although woody portions of roots act as an electrical barrier (also to microbial degradation), exchanges may occur during water uptake (in order to facilitate localized embolism repair in grapevines). Secondly, as discussed also in the introduction, some roots show anisotropic electrical conductivity, allowing current to flow radially more easily than longitudinally (Anderson and Higinbotham, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Field measurements were conducted in March 2017, using a 10-channel resistivity meter (Syscal Pro Switch 72, IRIS Instruments). For the 3-D scheme of ERT, a complete skip-two dipole-dipole scheme was adopted and produced some 5000 measurements, including reciprocal measurements used to estimate and reject bad data quality (Binley et al, 1995;Daily et al, 2004). A pulse duration of 250 ms for each measurement cycle and a target of 50 mV for potential readings were set as criteria for the current injection.…”
Section: The 3-d Scheme Of Ert and Malm Setup Acquisition And Processingmentioning
confidence: 99%
“…typically fourth order or higher roots) is possible (MacFall et al, 1990(MacFall et al, , 1991Cuneo et al, 2018) and might be particularly relevant when the absorption pathways of fine roots are scarce or damaged (Green & Clothier, 1999;Dubrovsky & North, 2002;Cuneo et al, 2016). Recently, direct evidence using micro-CT showed that water can enter woody roots through the lignified and suberized bark layer pointing to the water uptake potential of these roots (Cuneo et al, 2018). Direct evidence using magnetic resonance imaging (MacFall et al, 1990(MacFall et al, , 1991 and traditional hydraulic experiments (Queen, 1967;Chung & Kramer, 1975;Cuneo et al, 2018) showed similar results, thus we feel this is a feasible explanation for the recovery in Ψ stem in the drought-susceptible rootstock after re-watering.…”
Section: Researchmentioning
confidence: 99%
“…Previous studies have reported that water uptake through woody root portions (i.e. typically fourth order or higher roots) is possible (MacFall et al, 1990(MacFall et al, , 1991Cuneo et al, 2018) and might be particularly relevant when the absorption pathways of fine roots are scarce or damaged (Green & Clothier, 1999;Dubrovsky & North, 2002;Cuneo et al, 2016). Recently, direct evidence using micro-CT showed that water can enter woody roots through the lignified and suberized bark layer pointing to the water uptake potential of these roots (Cuneo et al, 2018).…”
Section: Researchmentioning
confidence: 99%
“…Could positive xylem pressure after rewatering repair embolism that has formed during a drought period? According to modelling studies, if an embolus is compressed to slightly above atmospheric pressure, it should be resorbed in seconds to minutes (Pickard, 1989; Yang & Tyree, 1992), and even atmospheric pressure can be sufficient for embolism repair, including via capillary forces (Rolland et al ., 2015; Knipfer et al ., 2016; Cuneo et al ., 2018). By contrast, stems with many emboli require many hours to refill (Tyree & Yang, 1992), and refilling may not be possible after severe drought stress that causes embolism in leaf veins as well as damage to the photosynthetic machinery, as observed in wheat (Johnson et al ., 2018).…”
Section: Role Of Positive Xylem Pressure In Recovery From Drought Andmentioning
confidence: 99%